DEVELOPMENT OF A WEB-BASED INVENTORY INFORMATION SYSTEM FOR A UNIVERSITY ROBOTICS LABORATORY: AN AGILE DEVELOPMENT APPROACH WITH ISO 25010 EVALUATION - Bian Dwi Pamungkas; Muhammad Alifi Ferdiansyah; Abdul Haris Indrakusuma; Vertika Panggayuh (STKIP PGRI TULUNGAGUNG, 2024)
Effective management of laboratory assets is a critical operational challenge in higher education institutions, particularly in engineering and robotics facilities where equipment is diverse, high-value, and subject to frequent use. Manual inventory practices remain prevalent in many university laboratories, leading to data inaccuracies, untracked loans, and difficulty in accountability. This study presents the development and evaluation of a web-based inventory information system for the Robotics Laboratory of Universitas Bhinneka PGRI. The system was developed using the Agile Development methodology, encompassing six iterative phases: Planning, Implementation, Testing, Documentation, Deployment, and Maintenance. The technology stack consisted of PHP with the Laravel 9 framework for the backend and Bootstrap 5 for the frontend, supported by a MySQL relational database. The system supports three role-based user levels — Administrator, Manager/Staff, and Member — and incorporates features for real-time item registration, loan management, return tracking, transaction approval workflows, and exportable reporting. System quality was evaluated using the ISO/IEC 25010 standard, specifically the Functional Suitability and Compatibility quality characteristics. Expert validation yielded scores of 99.16% and 100% for Functional Suitability and Compatibility, respectively, both classified as 'Very Feasible.' Usability was assessed using the System Usability Scale (SUS) with small-group (n=10, SUS=94.16) and large-group (n=30, SUS=93.50) tests, both falling within the 'Excellent' category. The findings demonstrate that the developed system substantially addresses the limitations of manual inventory management in robotics laboratory environments and provides a replicable model for similar institutional contexts.